A transferrin receptor-binding mucoadhesive elastin-like recombinamer: In vitro and in vivo characterization. (1st April 2019) - Gonzalez-Obeso, Constancio; Girotti, Alessandra; Rodriguez-Cabello, J. Carlos
Graphical abstract: Abstract: The development of mucoadhesive materials is of great interest and is also a major challenge. Being adsorption sites, mucosae are suitable targets for drug delivery, but as defensive barriers they are complex biological surfaces to interact with, mainly due to their protective mucus layer. As such, first- and second-generation mucoadhesives focused on material-mucus interactions, whereas the third generation of mucoadhesives introduced structural motifs that are able to interact with the cells beneath the mucus layer. The combination of different prerequisites (water solubility, soft gel formation at body temperature and able to interact with the mucus) in a single molecule is easily achieved using elastin-like recombinamers (ELRs) given their multiple block design. Moreover, we have been able to introduce a short amino-acid sequence known as T7 that is able to bind to transferrin receptors in the epithelial cell layer. The T7 sequence enhances the cell-binding properties of the mucoadhesive ELR (MELR), as demonstrated using a Caco-2 epithelial cell model. In vivo experiments confirmed the mucoadhesive properties found in vitro . Statement of Significance: The development of a mucoadhesive material is a major challenge. Mucosae are suitable targets for drug delivery, but as defense barriers, they are complex surfaces to interact with. In this work we report the first ELR that combines different functional blocks, in a single molecule, which provide it with the properties of soft-gel forming at body temperature and being able of efficiently adhering to the mucus layer of mucosas, as well as to the underlying epithelial cell layer, as demonstrated in vitro and in vivo . The rationally designed materials presented in this work sets the basis for developing ELR-based, mucosa-directed drug delivery systems, which could improve patient's compliance, enhancing drug retention at the mucosal site.